The Sexual Harassment of Female Active-Duty Personnel: Effects on Job Satisfaction and Intentions to Remain in the Military - Heather Antecol; Deborah A. Cobb-Clark (Institute for the Study of Labor (IZA), 2001)
This paper examines the relationship between sexual harassment and the job satisfaction and intended turnover of active-duty women in the U.S. military using unique data from a survey of the incidence of unwanted gender-related behavior conducted by the U.S. Department of Defense. Overall, 70.9 percent of active-duty women reported experiencing some type of sexually harassing behavior in the 12 months prior to the survey. Using singleequation probit models, we find that experiencing a sexually harassing behavior is associated with reduced job satisfaction and heightened intentions to leave the military. However, bivariate probit results indicate that failing to control for unobserved personality traits causes single-equation estimates of the effect of the sexually harassing behavior to be overstated. Similarly, including women?s views about whether or not they have in fact been sexually harassed directly into the single equation model reduces the estimated effect of the sexually harassing behavior itself on job satisfaction by almost a half while virtually eliminating it for intentions to leave the military. Finally, women who view their experiences as sexual harassment suffer additional negative consequences over and above those associated with the behavior itself.
Keywords: J28; J16; 330; Job satisfaction; sexual harassment; military employment; Frauenerwerbstätigkeit; Soldaten; Sexuelle Belästigung; Arbeitszufriedenheit; Schätzung; USA